Effect of supplemented sericin on the development, cell number, cryosurvival and number of lipid droplets in cultured bovine embryos. (3rd June 2016) - Hosoe, Misa; Inaba, Yasushi; Hashiyada, Yutaka; Imai, Kei; Kajitani, Kenji; Hasegawa, Yuichi; Irie, Mamoru; Teramoto, Hidetoshi; Takahashi, Toru; Niimura, Sueo
Abstract: Sericin was investigated as an alternative to fetal bovine serum (FBS) for bovine embryo culture. In vitro matured oocytes were developed using 0.05%, 0.1% or 0.15% sericin. The developmental rate, cryosurvival rate and blastulation time of these embryos were compared with those of embryos developed using 5% FBS. The number of lipid droplets was compared among the blastocysts developed using 5% FBS, using 0.05% sericin and in vivo . The rate of cleavage and blastocyst formation was similar among all groups. Blastulation occurred significantly earlier in the embryos developed using 5% FBS than in those developed using sericin at any concentration ( P  < 0.05). At 72 h after thawing, the cryosurvival rate of the blastocysts developed using 5% FBS and 0.05% sericin were significantly higher compared with those developed using 0.1% and 0.15% sericin ( P  < 0.05). The blastocysts developed using 0.05% sericin and in vivo produced a significantly fewer number of medium and large lipid droplets than those developed using 5% FBS. These results suggest that the blastocysts developed using 0.05% sericin show characteristics similar to those of the blastocysts developed in vivo and that the use of sericin as an alternative to FBS is feasible.